Taking a holistic view of the biblical perspectives on childlessness: Implications for Nigerian Christians and the church in Nigeria - Ademiluka, Solomon O. (HTS teologiese studies, 2021)
The belief amongst some Christians that it is God’s plan for everyone to have children, and that barrenness is a punishment from God is apparently derived from the Old Testament (OT). This article attempts a holistic study of the biblical perspectives on childlessness with a view to ascertain whether procreation is a moral responsibility of every individual. The target group includes Nigerian Christian couples suffering from infertility. The article employs the descriptive and exegetical methods. The study revealed that the belief that the OT views barrenness as caused by sin and a punishment from God was erroneous. A critical examination of the relevant texts revealed that infertility is a natural phenomenon, and God gives children as a blessing but not necessarily to every individual. In the New Testament (NT), the attitude towards childlessness is characterised by the concept of ‘alternative family models’, by which some Christians could adopt children whilst others might choose to be celibate, being satisfied with their membership of the community of believers. Paul’s teaching in 1 Corinthians 7 clearly mitigates natural childbearing, and thus negates any attitude of desperation for bearing children. In the Nigerian context, this interpretation necessitates a change of attitude towards infertility. The church has to develop a theological reconstruction with regard to procreation in marriage, in a manner that will assure Christians that a childless marriage is not lacking in any way.Contribution: The article is a contribution in the area of theology of marriage, and thus of high relevance in contemporary Africa, particularly Nigeria, where people, including Christians, still have the traditional belief that it is morally mandatory for everyone to have biological children.